Young Muslims, pedagogy and Islam contexts and concepts - Khan, M. G. (Muhammad G.) (Policy Press, 2013)
For most young people religion and religiosity is something latent or private, activated by private events or the passing of years. For Muslim young people it can be activated by an incessant Islamophobic discourse that requires fundamental questions of relationships and belonging to be addressed in the public gaze while being positioned as representatives and 'explainers' of their religion and their communities. This much-needed book discusses the realpolitik of developing services for young Muslims in the post-9/11 context and moves beyond notions of gendered provision and confessional activity to ask what defines a Muslim pedagogy. In doing so it presents a 'theoretical frame for Muslim youth work'.